When the Stars Came Home - Luby, Brittany; Donovan, Natasha (New York : Little, Brown and Company, 2023)
After his family moves to the city, young Ojiig misses the life he knew back home and the night sky full of stars until his parents help him find ways to make the city feel more like home.
Ages 4-8.
Keywords: Moving, Household -- Juvenile fiction; Stars -- Juvenile fiction; Ojibwa Indians -- Juvenile fiction; Indians of North America -- Juvenile fiction; Moving, Household -- Fiction; Stars -- Fiction; Ojibwa Indians -- Fiction; Indians of North America -- Fiction; Picture books